Assessment Of Magnitude and The Co-Morbidities of Overweight and Obesity in Urban and Rural Areas of Kanpur - Naresh Pal Singh; Pankaj K Jain; R P Sharma; Suresh Chandra; Seema Nigam; Anamika Singh (Medsci Publications, 2015)
Background: Obesity is emerging as a global epidemic with growing threat to health in both developed and developing countries. It has become a major health concern for almost all the age groups of the society. Objectives of the study is assess the prevalence and co-morbidities of overweight and obesity among persons 15 years and above in urban and rural areas of Kanpur, UP. Methods: For this cross-sectional study, multistage random sampling technique was used to select one colony in urban and one village in rural area of Kanpur district. The desired sample size was 2200. Detailed socio-demographic information was collected on a pre-designed and pre-tested questionnaire. After anthropometric examination, Body Mass Index (BMI) was used to assess the overweight and obesity status. Random blood sugar was measured using a portable glucometer. Data thus collected was analyzed using Chi-square test and percentage. Results: Statistically significant higher trend of obesity (BMI ≥ 30.0 kg/m2) was observed in urban population with total 2.9% (1.2% in males and 4.8% in females) in comparison to rural population with total 0.6% (0.4 % in males and 0.8% in females). Conclusions: Overweight and obesity is a complex multi-factorial disease developing from interactive influences of numerous factors in urban and rural settings.